Effect of frequency of intake and amount of fluoride in milk on enamel and dentine caries: in situ study - Cassiano, Luiza de Paula Silva (2014)
This study analysed the effect of frequency of intake and amount of fluoride in milk on the remineralisation of artificial enamel and dentine caries lesions in situ. Predemineralised bovine enamel and dentine slabs were randomly allocated to 5 in situ phases. Twenty-three subjects wore removable appliances with 2 enamel and 2 dentine slabs for 7 days each phase (separated by a 7-day washout period), following a crossover double-blind protocol. In each phase, treatment was performed with milk containing 2.5 ppm fluoride (F) everyday (T1), 2.5 ppm F every other day (T2), 5.0 ppm F every day (T3), 5.0 ppm F every other day (T4) or no treatment (control; T5). The subjects were instructed to immerse the appliance in 100 ml of milk for 5 minutes and then drank 200 ml of the respective milk. The enamel alterations were quantified by surface hardness (%SHR) and transversal microradiography (TMR, Z) and dentine by TMR only. Data were analysed by repeated-measures ANOVA/Tukey´s tests (p<0.05). For enamel, the highest %SHR was found for groups treated with fluoridated milk every day compared to control, without significant differences between T1 and T3. All groups showed positive values of Z, except for T4; significant differences were seen between T1/T3 and T4. For dentine, the only group that presented remineralisation was T2. Fluoridated milk every day seems to have better remineralising effect on enamel than its use every other day, but no dose-response effect was seen. Dentine, however, does not seem to benefit from every day use of fluoridated milk.